Soliton Dynamics of the Generalized Shallow Water Like Equation in Nonlinear Phenomenon - Akram, Ghazala; Sadaf, Maasoomah; Khan, M. Atta Ullah (Frontiers in Physics, 2022)
The generalized shallow water-like equation is investigated in this research paper. Exact solutions of generalized shallow water-like equation are extracted using modified auxiliary equation (MAE) method and extended ( G′ G2 )-expansion method. Many novel soliton solutions are obtained using these methods. The retrieved solution of governing model include rational, trigonometric and hyperbolic functions. The 3D graphs and 2D contour graphs of obtained solutions are plotted using symbolic software such as Maple. The aim of plotting graphs is to demonstrate the dynamical behavior of acquired solutions. Thus, this study investigate the exact soliton solutions of generalized shallow water-like using proposed methods.